SYNTHESIS OF POLYPROPYLCALIX[6]ARENE FROM p-t-BUTYLPHENOL AS ADSORBENT FOR Cr(III) METAL ION - Susy Yunita Prabawati; Jumina Jumina; Sri Juari Santosa; Mustofa Mustofa (Indonesian Journal of Chemistry, 2011)
A study has been conducted to synthesize a novel polypropylcalix[6]arene polymer using p-t-butylphenol as a starting material. It was of interest to investigate the capability of the polymer with a tunnel-like structure, as adsorbent to trap the heavy metal cation such as Cr3+. The synthesis was carried out in several steps i.e (1) formation of p-t-butylcalix[6]arene from p-t-butylphenol as a starting material, (2) treatment of p-t-butylcalix[6]arene with 4.95 equivalents of allyl bromide under  alkaline conditions to yield p-t-butyl-37,40-diallyloxy-38,39,41,42-tetra-hydroxy-calix[6]arene, and (3) polymerization of p-t-butyl-37,40-diallyloxy-38,39,41,42-tetrahydroxycalix[6]arene by treatment with concentrated sulfuric acid to yield polypropyl-calix[6]arene. The application of polypropylcalix[6]arene for trapping Cr(III) was investigated by stirring the suspension of calixarene under variation of pH, time, and adsorbent mass. IR and 1H NMR spectra, showed that two allyl groups had been incorporated to the lower rim of the p-t-butylcalix[6]arene and the polymer was obtained as brownish green crystals with the melting point of 108-110 °C. The study also showed that the polypropylcalix[6]arene was able to trap Cr(III) cation. The optimum adsorption conditions were achieved at pH 5, contact time 60 min and concentration 12 mg/l for every 0,008 g of polymer.